2020
DOI: 10.1088/1751-8121/ab93fd
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the conditional mutual information in ballistic and diffusive non-equilibrium steady-states

Abstract: The conditional mutual information (CMI) I(A : C|B) quantifies the amount of correlations shared between A and C given B. It therefore functions as a more general quantifier of bipartite correlations in multipartite scenarios, playing an important role in the theory of quantum Markov chains. In this paper we carry out a detailed study on the behavior of the CMI in non-equilibrium steady-states (NESS) of a quantum chain placed between two baths at different temperatures. These results are used to shed light on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…It has been shown that, in composite quantum systems, entropy production is related to the internal correlation between subsystems [20,23,25]. We show that the parametric amplification process not only modifies the internal correlation between the subsystems, but also produces an additional correlation between non-commuting observables (q and p) of the parametrically driven oscillator.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…It has been shown that, in composite quantum systems, entropy production is related to the internal correlation between subsystems [20,23,25]. We show that the parametric amplification process not only modifies the internal correlation between the subsystems, but also produces an additional correlation between non-commuting observables (q and p) of the parametrically driven oscillator.…”
Section: Introductionmentioning
confidence: 81%
“…More recently, considerable attention has been directed towards the theoretical and experimental characterization of entropy production in non-equilibrium bosonic systems based on the quantum phase space distributions and Fokker-Planck equations [18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…To calculate the dynamics of the covariance matrix and the vector of means of a linear system, the standard approach consists of taking into account that Ȯ = Tr[ Ô Lρ(t)] for the particular Liouvillian L of the model under study, and consider both Ô = xj and Ô = xj xk to find a closed system of equations for x and V (see, e.g., Refs. [42,43]). Such an approach is often cumbersome and time-consuming, and completely lacks generality.…”
Section: Linear Dynamics Of Bosonic Systemsmentioning
confidence: 99%
“…The time evolution of C can be obtained directly from Eq. ( 5) (see [16,49,54] for details), and reads…”
Section: B Steady-state Equation For the Covariance Matrixmentioning
confidence: 99%